Bmal1 Regulates Macrophage Polarize Through Glycolytic Pathway in Alcoholic Liver Disease - Zhou, Yiwen; Wu, Meifei; Xu, Lei; Cheng, Jieling; Shen, Jie; Yang, Tianyu; Zhang, Lei (Frontiers in Pharmacology, 2021)
Hepatic macrophages play a critical role in inflammation caused by alcohol feeding. During the process, the change of macrophage phenotype affects the inflammatory response in different ways. Moreover, there is increasing evidence that Brain and Muscle Arnt-Like Protein-1 (Bmal1) is regarded as a key regulator of macrophage transformation. In our study, Bmal1 was detected to be low expressed in EtOH-fed mice tissue samples and ethanol-induced RAW264.7 cells. Hepatic specific overexpression of Bmal1 significantly reduced the expression of M1 macrophage markers and increased the expression of M2 macrophage markers. Furthermore, alcoholic liver lesions were also improved in alcohol feeding mice with overexpressed Bmal1. On this basis, we also found that the glycolytic pathway can regulate macrophage polarization. In vitro, blocking of glycolytic pathway can significantly inhibit M1-type polarization. Importantly, glycolysis levels were also restrained after Bmal1 overexpression. What's more, Bmal1 interacts with glycolysis via S100A9 protein. Further studies showed that the alleviation of alcoholic liver disease (ALD) by Bmal1 was associated with glycolytic pathway suppression and M1 macrophage polarization. In summary, we demonstrated that Bmal1 is a gene capable of relieving ALD, and this effect may provide new insights for altering macrophage phenotypes to regulate inflammatory responses in ALD.